DEVELOPMENT OF INDONESIA e-LKPD BASED ON LOCAL WISDOM - Nazara, Anariati; Harefa, Noveri Amal Jaya; Bu'ulolo, Yanida; Zega, Imansudi (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
This research aims to develop practical and effective teaching materials in the form of E-LKPD products based on local wisdom on Fable Story material in class VII of SMP Negeri 1 Afulu. The research method used is the research and development method or better known as Research and Development (R&D). The development model that researchers will use is the ADDIE procedural model. The stages of the ADDIE research model are the analysis stage, design stage, development stage, implementation stage and evaluation stage. The instruments used by researchers are validation questionnaires for material experts, language experts, design experts, student response questionnaires and effectiveness questionnaires for student learning outcomes. The research results of the E-LKPD product that has been developed obtained very valid criteria by material validators with a percentage of 97%, language validators 96% and design/media validators 100%. The E-LKPD product was stated to be very practical, obtained from student response questionnaires, namely small group trials of 94.4%, and field trials of 95.4%. Furthermore, E-LKPD was declared very effective, obtained from the results of student learning tests which consisted of 2 stages, namely small group trials at 83.3% and field tests at 91.6%. From the results of the research above, the local wisdom-based E-LKPD that was developed meets the criteria of being valid, practical and effective for use in Indonesian language learning and meets the research objectives.